Analysis of Dopant Atom Distribution and Quantification of Oxygen Vacancies on Individual Gd‐Doped CeO2 Nanocrystals. Issue 21 (14th May 2014) - Stroppa, Daniel G.; Dalmaschio, Cleocir J.; Houben, Lothar; Barthel, Juri; Montoro, Luciano A.; Leite, Edson R.; Ramirez, Antonio J.
Abstract This work reports the analysis of the distribution of Gd atoms and the quantification of O vacancies applied to individual CeO2 and Gd‐doped CeO2 nanocrystals by electron energy‐loss spectroscopy. The concentration of O vacancies measured on the undoped system (6.3±2.6 %) matches the expected value given the typical Ce3+ content previously reported for CeO2 nanoparticles. The doped nanoparticles have an uneven distribution of dopant atoms and an atypical amount of O vacant sites (37.7±4.1 %). The measured decrease of the O content induced by Gd doping cannot be explained solely by the charge balance including Ce3+ and Gd3+ ions.